Penerapan Metode TOPSIS Penentuan Pemberian Mikro Faedah Bank Syariah Indonesia (BSI) - Afriany, Joli; Tampubolon, Kennedi; Fadillah, Rizkah (TIN: Terapan Informatika Nusantara, 2021)
The Faedah Micro Loan at Bank Syariah Indonesia is a program that is certainly an advantage for the customer and the bank as well. For this reason, an assessment is needed as a material for consideration or selection of prospective customers who are entitled to receive these loans through various predetermined criteria. Given the risk of uncollectible loans to customers is quite large. So to help determine someone who is entitled to receive a loan, a decision support system is needed. To calculate the feasibility of each prospective customer, the method used for the decision support system is the Technique for Orders Preference by Similarity to Ideal Solution (TOPSIS) method. The TOPSIS method has a simple and easy-to-understand concept, this simplicity can be seen from the less complicated process flow. In this study, a search case will be discussed for each of the best alternative prospective customers who are entitled to receive a loan based on the criteria that have been determined using the TOPSIS method. The criteria used in the study were administrative completeness, marital status, savings books, guarantees and business income, then the weight values ​​of all these criteria were calculated. The results of the study indicate that the fifth alternative is the highest alternative with a value of 0.873.